POSITIVISME: LANDASAN FILOSOFIS DAN IMPLIKASINYA PADA METODE ILMIAH - Andi Yaksa, Rully; Fitrah, Yundi; Kusuma, Ade; Ayu Wulandari, Bunga (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to analyze the implications of positivism on the scientific method through a literature review. Positivism, a philosophical school developed in the 19th century by Auguste Comte, emphasizes the importance of empirical observation, verification, and objectivity in acquiring scientific knowledge. This study is important because it provides a better understanding of how positivism influenced the scientific method and how this method developed and is used in the contemporary academic world. Through this literature review, the research explores the history of positivism, its core principles, and its contributions to the scientific method in both natural and social sciences. Additionally, critiques of positivism by philosophers such as Karl Popper and Thomas Kuhn are analyzed, particularly in relation to its limitations in addressing complex and subjective phenomena. The findings indicate that while positivism has played a significant role in the development of science, the more flexible post-positivist approach is increasingly relevant in addressing contemporary scientific research challenges.